2014
DOI: 10.1073/pnas.1407351111
|View full text |Cite
|
Sign up to set email alerts
|

Polarized deposition of basement membrane proteins depends on Phosphatidylinositol synthase and the levels of Phosphatidylinositol 4,5-bisphosphate

Abstract: The basement membrane (BM), a specialized sheet of the extracellular matrix contacting the basal side of epithelial tissues, plays an important role in the control of the polarized structure of epithelial cells. However, little is known about how BM proteins themselves achieve a polarized distribution. Here, we identify phosphatidylinositol 4,5-bisphosphate (PIP2) as a critical regulator of the polarized secretion of BM proteins. A decrease of PIP2 levels, in particular through mutations in Phosphatidylinosito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
42
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 41 publications
5
42
0
Order By: Relevance
“…Drosophila ColIV consists of two a chains, a-1 (Cg25c) and a-2 (Vkg), which form heterotrimers (Blumberg et al, 1988;Lunstrum et al, 1988) that are post-translationally modified by lysyl and prolyl hydroxylases enzymes, ultimately forming a functional BM (Bunt et al, 2010;Lerner et al, 2013;Pastor-Pareja and Xu, 2011). In adult ovaries, somatic follicular cells produce (legend continued on next page) ColIV, which is basally assembled into an egg chamber BM network through a Crag/Rab10/PIs-dependent mechanism (Denef et al, 2008;Devergne et al, 2014;Lerner et al, 2013;Medioni and Noselli, 2005). This specific ColIV plays an essential role in the establishment and maintenance of follicle cell polarity and in promoting egg elongation (Haigo and Bilder, 2011;Horne-Badovinac et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Drosophila ColIV consists of two a chains, a-1 (Cg25c) and a-2 (Vkg), which form heterotrimers (Blumberg et al, 1988;Lunstrum et al, 1988) that are post-translationally modified by lysyl and prolyl hydroxylases enzymes, ultimately forming a functional BM (Bunt et al, 2010;Lerner et al, 2013;Pastor-Pareja and Xu, 2011). In adult ovaries, somatic follicular cells produce (legend continued on next page) ColIV, which is basally assembled into an egg chamber BM network through a Crag/Rab10/PIs-dependent mechanism (Denef et al, 2008;Devergne et al, 2014;Lerner et al, 2013;Medioni and Noselli, 2005). This specific ColIV plays an essential role in the establishment and maintenance of follicle cell polarity and in promoting egg elongation (Haigo and Bilder, 2011;Horne-Badovinac et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…This possibility is appealing as it aligns well with the likely function of Rab10. Alternatively, Scarface could function at the apical plasma membrane to prevent targeting of BM-containing vesicles to this domain, a function that has also been proposed for Crag (Denef et al, 2008; Devergne et al, 2014). Finally, Scarface could remove BM proteins from the apical surface either by stimulating a proteolytic cascade or via endocytosis.…”
Section: Synthesis Secretion and Assembly Of Bms On Basal Cell Sumentioning
confidence: 99%
“…Two additional proteins have been identified that are required for polarized BM secretion, although the mechanisms by which they do so are less well understood. These are Phosphatidylinositol synthase (Pis), an enzyme involved in the production of phosphoinositides (Devergne, Tsung, Barcelo, & Schupbach, 2014), and Scarface, a secreted serine protease-like protein that lacks catalytic activity (Sorrosal et al, 2010). …”
Section: Synthesis Secretion and Assembly Of Bms On Basal Cell Sumentioning
confidence: 99%
See 2 more Smart Citations